Disappearance of dry matter from mature oat crops grazed by ewes in summer: Preliminary results - Andueza D.; Muñoz F.; Delgado I.; Treacher T. (Recent advances in small ruminant nutrition, 1997)
The objective of the experiment was to study the rate of disappearance of dry matter from the head, leaf and stem fractions of mature oat crops during grazing by sheep in a semi-arid, non-irrigated region of Aragon (Spain). Between June and August 1995, measurements were made on 30 tillers chosen at random in two plots that were grazed continuously by 17 dry ewes for 50 days in plot 1, and for 21 days in plot 2. On each tiller the height of the stem, length of each leaf and the number of spikelets were measured weekly. The length measurements were converted to weights of the three fractions, spikelets, leaf and stem, using weights of individual spikelets, hereafter termed head, and weights per unit length of leaf and stem obtained dissecting, measuring and weighing segments of 50 tillers selected at random at each sampling date. The results demonstrated differences between the plots in initial weight of tillers and proportions of head, leaf and stem and in the patterns of disappearance of the fractions during grazing.
Seminar of the FAO-CIHEAM Network of Cooperative Research on Sheep and Goats, Subnetwork on Nutrition, 24-26 Oct 1996, Rabat (Morocco)